2008
DOI: 10.1007/s00198-008-0652-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and bone mineral density among Hispanic men

Abstract: Introduction-Disparities within ethnic groups are generally ignored, but in evolving populations they may have implications for public health. We examined ethnic variation in serum 25-hydroxyvitamin D [25(OH)D] and bone mineral density (BMD) among Hispanic American men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
2
8
1
1
Order By: Relevance
“…In a study conducted in South Florida, vitamin D deficiency was more prevalent in Hispanics [32], although 25(OH)D levels were measured using a DiaSorin radioimmunoassay method. Recently, a study in a group of 358 Hispanic American men found the highest prevalence of vitamin D deficiency (<20 ng/ml or <50 nmol/l) among Puerto Ricans (26%), compared to those from the Dominican Republic (21%), Central America (11%) and South America (9%) [33]. Furthermore, recent data from the National Health and Nutrition Examination Survey, which measured 25(OH)D levels by a competitive binding protein assay, found vitamin D insufficiency (<30 ng/ml or <75 nmol/l) in 97% of non-Hispanic Blacks and 90% of Mexican Americans [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in South Florida, vitamin D deficiency was more prevalent in Hispanics [32], although 25(OH)D levels were measured using a DiaSorin radioimmunoassay method. Recently, a study in a group of 358 Hispanic American men found the highest prevalence of vitamin D deficiency (<20 ng/ml or <50 nmol/l) among Puerto Ricans (26%), compared to those from the Dominican Republic (21%), Central America (11%) and South America (9%) [33]. Furthermore, recent data from the National Health and Nutrition Examination Survey, which measured 25(OH)D levels by a competitive binding protein assay, found vitamin D insufficiency (<30 ng/ml or <75 nmol/l) in 97% of non-Hispanic Blacks and 90% of Mexican Americans [34].…”
Section: Discussionmentioning
confidence: 99%
“…Populations that shield themselves from solar exposure or who have pigmented skin are at increased risk for vitamin D deficiency [Looker et al, 2002]. Some of these groups may experience greater deleterious effects of low 25OHD levels on bone mineral density [Araujo et al, 2009]. In addition to these aforementioned effects in children and adults, there is increasing data that maternal vitamin D deficiency can affect in utero skeletal development.…”
Section: Clinical Skeletal Effects Of Vitamin Dmentioning
confidence: 99%
“…1015 Among 358 Hispanic-American men, the highest prevalence of vitamin D deficiency was found among those born in PR (26%), compared to those from the Dominican Republic (21%), Central America (11%), and South America (9%). 16 Recently, we found in a large sample of 2,293 adults in PR that 72% had vitamin D insufficiency (levels below 30 ng/ml) and 28% were vitamin D deficient. 17 …”
Section: Introductionmentioning
confidence: 99%